1999
DOI: 10.1001/archpsyc.56.11.981
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Abnormalities in Patients With Early Alzheimer Disease

Abstract: Background: Deficits in somatostatin-like immunoreactivity (SLI) and corticotropin-releasing factor immunoreactivity (CRF-IR) are well recognized as prominent neurochemical deficits in Alzheimer disease (AD). The question of whether these profound neuropeptidergic deficits found in patients with end-stage disease extend into those with much earlier disease is relatively unanswered. To determine the relation between level of SLI and CRF-IR in different cerebrocortical regions to the earliest signs of cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 36 publications
(38 reference statements)
0
44
0
1
Order By: Relevance
“…This suggests that interactions between neurotransmitter systems are significant for the production of adaptive behavior (Decker and McGaugh, 1991). The findings also suggest a link between the cognitive and behavioral impairments that occur in Alzheimer disease and the fact that multiple neurotransmitter systems such as cholinergic, noradrenergic, and serotonergic systems are typically impaired in the brain of Alzheimer patients (Chen et al, 2000;Davis et al, 1999;Dringenberg, 2000;Francis et al, 1999;Lai et al, 2002;Reinikainen et al, 1990). Our previous studies confirmed that neither PRO nor pCPA given individually impaired WM performance, and that scopolamine impaired naive but not WM strategiespretrained rats (Beiko et al, 1997;Saber and Cain, 2003).…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…This suggests that interactions between neurotransmitter systems are significant for the production of adaptive behavior (Decker and McGaugh, 1991). The findings also suggest a link between the cognitive and behavioral impairments that occur in Alzheimer disease and the fact that multiple neurotransmitter systems such as cholinergic, noradrenergic, and serotonergic systems are typically impaired in the brain of Alzheimer patients (Chen et al, 2000;Davis et al, 1999;Dringenberg, 2000;Francis et al, 1999;Lai et al, 2002;Reinikainen et al, 1990). Our previous studies confirmed that neither PRO nor pCPA given individually impaired WM performance, and that scopolamine impaired naive but not WM strategiespretrained rats (Beiko et al, 1997;Saber and Cain, 2003).…”
Section: Introductionmentioning
confidence: 51%
“…However, the current use of anticholinesterase drugs to improve cholinergic function has not been fully effective for many patients, and debate continues about their costeffectiveness (AD2000 Collaborative Group, 2004). This is probably because Alzheimer disease typically involves the vast loss of synaptic contacts in cortex and elsewhere that normally release a number of brain neurotransmitter and neuropeptide systems including cholinergic, serotonergic, b-adrenergic, somatostatinergic, and GABAergic systems (Chen et al, 2000;Davis et al, 1999;Francis et al, 1999;Reinikainen et al, 1990), and this loss of multiple, often interacting systems may be important for the severe cognitive and behavioral impairments in Alzheimer patients. If true, optimal pharmacological treatment will require agents directed at a number of different systems in combination.…”
Section: Implications For Alzheimer Diseasementioning
confidence: 99%
“…This early principal cell neurodegeneration in the entorhinal cortex was previous to that seen in hippocampus (18 months) as described in AD patients. Moreover, both brain areas in this transgenic mice display a prominent early reduction of SOM/NPY interneurons of GABA system [3,4] as occurs in AD brains [5][6][7][8][9][10][11][12]. Therefore, this PS1/AβPP mouse could mimic the initial stages of the pathology in humans and could be of great interest to analyze the age-dependent vulnerability of different neuronal subpopulations to this disease.…”
Section: Introductionmentioning
confidence: 87%
“…The CRF family of signaling molecules is broadly involved in physiological and behavioral responses to stress (Chadwick et al, 1993) and undergoes alterations early in AD progression (Davis et al, 1999). However, the nature of its involvement in AD neuropathology is unclear.…”
Section: Crfrs Differentially Regulate Stress-induced Tau Phosphorylamentioning
confidence: 99%